2011
DOI: 10.1093/humupd/dmr027
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association studies of angiogenesis- and vasoconstriction-related genes in women with recurrent pregnancy loss: a systematic review and meta-analysis

Abstract: Meta-analyses of available data showed significant associations between the VEGF (-1154G>A), p53 (codon72) and eNOS (Glu298Asp) polymorphisms and idiopathic RPL. These angiogenesis- and vasoconstriction-related genes jointly confer higher susceptibility to idiopathic RPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 63 publications
7
107
1
2
Order By: Relevance
“…This reduction is reportedly associated with various vascular diseases such as myocardial infarction (Shimasaki et al, 1998), placental abruption (Yoshimura et al, 2001), and pre-eclampsia (Yoshimura et al, 2000;Savvidou et al, 2001). A meta-analysis has revealed a close association between rs1799983 and idiopathic RM (Su et al, 2011). Our results demonstrated that RM patients had a significantly lower frequency of the G allele of rs1799983, which is consistent with previous studies in Koreans (Shin et al, 2010), whites (Hefler et al, 2002), and Indians (Parveen et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This reduction is reportedly associated with various vascular diseases such as myocardial infarction (Shimasaki et al, 1998), placental abruption (Yoshimura et al, 2001), and pre-eclampsia (Yoshimura et al, 2000;Savvidou et al, 2001). A meta-analysis has revealed a close association between rs1799983 and idiopathic RM (Su et al, 2011). Our results demonstrated that RM patients had a significantly lower frequency of the G allele of rs1799983, which is consistent with previous studies in Koreans (Shin et al, 2010), whites (Hefler et al, 2002), and Indians (Parveen et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…The rs1799983 SNP is associated with various vascular diseases related to pregnancy (Yoshimura et al, 2001;Hefler et al, 2002;Hillermann et al, 2005;Huber et al, 2005;Suryanarayana et al, 2006). A systematic review has indicated that rs1799983 may be correlated with recurrent spontaneous abortion (Su et al, 2011). The rs2070744 SNP has been observed in patients with vascular disease (Khurana et al, 2003;Rossi et al, 2003;Guang-Da et al, 2005); it inhibits the promoter activity of eNOS.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of VEGF-A and VEGF-C has been demonstrated in the human endometrium throughout the menstrual cycle with an increase in the late proliferative and secretory phases (13,14). In addition, VEGF's expression was found in decidual cells of early pregnancy (15). On the other hand, expression of VEGF receptors was shown in human endometrium (13).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the included studies was assessed according to the following criteria from the previous meta-analysis [28]: …”
Section: Data Extractionmentioning
confidence: 99%